La mesa consultiva- Sentencia T-052/2017: una experiencia de construcción territorial entre los indígenas Barí y la asociación campesina del Catatumbo ASCAMCAT - Merly Zoraida Gelvez Santiago; Javier Alonso Santiago Velásquez; José Manuel Alba Maldonado (Mundo Fesc)
The Catatumbo region develops under different cultures and worldviews, where peasants and Indigenous peoples have suffered the effects of war without distinction, interweaving relationships over the years. This article aims to identify the processes of territorial construction, based on the dialogues established in the advisory table, established through the Constitutional Court ruling T052 of 2017, from the proposals for expansion, delimitation, and sanitation of the territory of the Motilón Bari Indigenous people and the constitution of the Peasant Reserve Zone by the Catatumbo Peasant Association. This proposal is developed under a qualitative methodological design, which allows for the construction of knowledge based on different forms of information collection, within a hermeneutic approach. leaving as a result the evidence of the existing relationships between the Barí indigenous people and the peasants, which marked the path to the development of sentence T 052 of 2017, the interpretations and tensions, that this unleashed between the parties and the intercultural dialogues carried out to arrive at the construction from the recognition and thus create alternative development proposals for the territories they share, facing the challenges for compliance with sentence T052 / 2017. This text is a vision of the peasantry, built from the experience of the Peasant Association of Catatumbo.